New species of the genus Eupithecia (Lepidoptera, Geometridae) from China. Part IX - Mironov, Vladimir; Šumpich, Jan (Zootaxa, 2022)
In this ninth part of this series, six new species of Eupithecia Curtis, 1825 are described from China: Eupithecia remissata sp. n., Eupithecia fericlava sp. n., Eupithecia florianii sp. n., Eupithecia concostivexa sp. n., Eupithecia voraria sp. n. and Eupithecia khama sp. n. The species Eupithecia solianikovi Viidalepp, 1988 is recorded as new for China. Eupithecia fulvidorsata Mironov & Galsworthy, 2006 is a first record for Yunnan province and two species Eupithecia ensifera Mironov & Galsworthy, 2004 and Eupithecia supercastigata Inoue, 1958 are recorded from Sichuan province for the first time. Adults and genitalia are illustrated for all species.